Corruption and Foreign Direct Investment:What kind of relationship is there? - Caetano, José Manuel Martins (2013)
Globalization and technological innovations create investment opportunities for firms worldwide. In fact, while firms pursue foreign direct investment (FDI) opportunities on a global basis, countries compete to attract these flows. Investment decisions by firms depend on complex and distinct factors. In particular, in the case of foreign investment one of these factors relates to the perception that investors have about the level of risk and/or corruption (or transparency) that characterises countries. Recent studies suggest that corruption negatively impacts on FDI and may act as a disincentive to investment. By using information for 97 countries, concerning inward FDI performance and perceived level of corruption, this paper intends to analyse how corruption influences on the FDI. Given that a certain level of perceived corruption can, in fact, be subject to different subjective evaluations by investors, the paper uses a fuzzy logic approach in order to determine conceivable clusters in the FDI-corruption space. The use of fuzzy clustering techniques reveals the existence of two well-defined clusters: one is formed by high-level corruption countries, where, indeed, corruption is negatively correlated, in a significant way, with FDI; the other is formed by low-level corruption countries, where the influence of corruption on FDI is not so evident.